Panax ginseng improves physical recovery and energy utilization on chronic fatigue in rats through the PI3K/AKT/mTOR signalling pathway. (31st December 2023) - Zhang, Guolei; Lu, BoFan; Wang, Enhui; Wang, Wei; Li, Zheng; Jiao, Lili; Li, Hui; Wu, Wei
Abstract: Context: Panax ginseng C. A. Meyer (Araliaceae) is a tonic herb used in ancient Asia. Objective: This study investigated the antifatigue effect of P. ginseng on chronic fatigue rats. Materials and methods: Sprague-Dawley rats were divided into control, model and EEP (ethanol extraction of P. ginseng roots) (50, 100 and 200 mg/kg) groups ( n = 8). The rats were subcutaneously handled with loaded swimming once daily for 26 days, except for the control group. The animals were intragastrically treated with EEP from the 15th day. On day 30, serum, liver and muscles were collected, and the PI3K/Akt/mTOR signalling pathway was evaluated. Results: The swimming times to exhaust of the rats with EEP were significantly longer than that without it. EEP spared the amount of muscle glycogen, hepatic glycogen and blood sugar under the chronic state. In addition, EEP significantly ( p < 0.05) decreased serum triglycerides (1.24 ± 0.17, 1.29 ± 0.04 and 1.20 ± 0.21 vs. 1.58 ± 0.13 mmol/L) and total cholesterol (1.64 ± 0.36, 1.70 ± 0.15 and 1.41 ± 0.19 vs. 2.22 ± 0.19 mmol/L) compared to the model group. Regarding the regulation of energy, EEP had a positive impact on promoting ATPase activities and relative protein expression of the PI3K/Akt/mTOR pathway. Conclusions: Our results suggested that EEP effectively relieved chronic fatigue, providing evidence that P. ginseng could be a potential dietary supplement to accelerate recovery from fatigue.